Desenvolvimento de eletrodo FGM a base de Ni-zircônia para célula a combustível de sólido óxido - Lima, Andressa Bastos da Mota (2007)
The search for alternatives sources to fossil fuel has stimulated the technological development of solid oxide fuel cell. Hydrogen is the ideal fuel for this application. However, due to technical reasons, alternatives fuels to hydrogen such as methanol and natural gas has been tested. Therefore, the use of these fuels makes necessary the substitution of the anode materials that are normally used with hydrogen. The anode materials substitution must be based on the knowledge about the relationship between anode microstructure and its performance during cell operation. This knowledge makes possible introduce new materials besides new fabrication process for solid oxide fuel cell anodes. The main characteristics of anode are: high chemical activity and durability. The durability of the anode can be attained using FGM material that makes possible to match the thermal expansion of the interfaces. Ni-8YSZ cermet is normally used as anode material. In this work it was studied the cermets Ni-8YSZ as electrodes on the YSZ electrolyte. Two types of electrodes were prepared: with and without compositional gradient along the electrode thickness. This work was developed in two steps. The first one was the development of the powder 8YSZ-NiO suspension with the appropriated rheological characteristics. The second one was the electrodes characterization by impedance spectroscopy and scanning electron microscopy. It was found that electrodes containing layers with ≤30 vol% Ni are inefficient to promote the reactions because de Ni particles are not percolated.